Republic of Latvia : 2006 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Latvia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The Latvian economy has made remarkable strides, combining macroeconomic stability with rapid income convergence. An upfront policy tightening is needed to contain near-term overheating and secure a soft landing. Fiscal restraint is needed to counter the sizable demand stimulus already in play. Moderating credit growth is essential to relieve overheating pressures. Risks from the credit boom and delayed euro adoption reinforce the need for a strong regulatory and supervisory framework for banks. Safeguarding competitiveness while narrowing the wage gap requires scaling the technology ladder.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet